Repair of Iris Defects - Tushar Agarwal; Tarun Arora (Delhi Journal of Ophthalmology)
Purpose: To demonstrate three techniques of repair of iris defects in cases with iridodialysis, post surgical coloboma and post-traumatic mydriasis. Methods: Video-based description of repair of three cases of iris defects, highlighting the technique and difficulties in performing surgery in these cases. Results: In the first case with post-traumatic subluxated cataract and iridodialysis, ICCE and iridodialysis repair was performed successfully. The second case had surgical coloboma and aphakia due to previous complicated cataract surgery. Repair of the coloboma and implantation of ACIOL was performed successfully. Third case presented with a post-traumatic cataract and sphincter tear associated with mydriasis. PCIOL implantation along with mydriasis repair was performed. Conclusions: With the help of these techniques, sutures can be used to repair iridodialysis, colobomatous defects, and mydriatic pupils. Results in these patients are very gratifying. Patients appreciate the reduction in light and glare sensitivity in the immediate post-operative period